Humanism in Intercultural Perspective: Experiences and Expectations - Laass, Henner; Rüsen, Jörn (Der Mensch im Netz der Kulturen - Humanismus in der Epoche der Globalisierung / Being Human: Caught in the Web of Cultures - Humanism in the Age of Globalization, 2009)
This book is a breakthrough in illuminating humanism. For the first time it is presented in an intercultural perspective. It introduces Chinese, Indian, African, Islamic, and Western traditions into the intercultural discussion about basic issues of understanding the human world. By this means it recognizes different disciplinary perspectives: history, philosophy as well as religious, literary and gender studies. Special emphasis is put on the controversial relationship between humanism and religion. This complex network of argumentations is an answer to the challenge of cultural orientation at the age of globalization. Humanism is brought to life as a synthesis of transcultural values and a mutual and critical recognition of cultural differences.